Mass Media as Educational and Political Agent: A Literature Review on its Functions, Benefits, and Challenges in Education - Shofuro, Aty Lu’lu; Rokhmatiah, Hawa; Putri, Lyra Nabila (UM Purwokerto Press, 2025)
Mass media plays a strategic role in shaping the direction of educational development and democracy in the digital era. Not only as a conveyor of information, mass media also functions as an educational and political agent that influences the mindset, attitudes, and participation of the community, especially the younger generation. Through various platforms such as television, radio, newspapers, online media, and social media, mass media help shape academic culture, expand access to educational information, and increase political awareness among students. This research aims to examine the role, benefits and challenges of mass media in the context of education. The study is conducted through a literature review of various scientific sources that discuss media involvement in learning, character education, political information dissemination, and public opinion formation. The results show that mass media plays an important role in increasing digital literacy, interest in learning, creativity, and creativity.